SURGICAL TREATMENT OF CEREBRAL PALSY - KH.T. GANIEV; A.A. RAZZOKOV (Паёми Сино, 2024)
Objective: To improve surgical treatment outcomes of spastic cerebral palsy (SCP) with lower extremities involvement